Answer:
(6, 2 )
Explanation:
3x - 2y = 14 → (1)
5x + 6y = 42 → (2)
multiply (1) through by - 1
- 3x + 2y = - 14 ( add 3x to both sides )
2y = 3x - 14
substitute 2y = 3x - 14 into (2)
5x + 3(2y) = 42
5x + 3(3x - 14) = 42
5x + 9x - 42 = 42
14x - 42 = 42 ( add 42 to both sides )
14x = 84 ( divide both sides by 14 )
x = 6
substitute x = 6 into either of the 2 equations and solve for y
substituting into (2)
5(6) + 6y = 42
30 + 6y = 42 ( subtract 30 from both sides )
6y = 12 ( divide both sides by 6 )
y = 2
solution is (6, 2 )